Avifaunal diversity in and around Chargaon Dam (Warora) District Chandrapur (M.S.) India. - Bawaskar Kiran S; Khate Dinesh; Wazalwar Sachin (International Journal of Life Sciences, 2016)
This paper deals with the community of birds in and around Chargaon dam Warora district Chandrapur Maharashtra state India. It is situated at coordinate 20.3944526°N 79.1757202°E district of Maharashtra India. In present no data pertaining to avifaunal diversity of this region is available, so that we were decided to prepare a checklist of birds. The observation was carried out throughout year from April 2012- April 2016 in and around Chargaon dam. The study revealed a total 196 species of birds belonging to the 64 families and 19 orders of which 139 Species were resident 17 Migratory residents 38 winter migratory 1 breeding migratory and 1 species were passage migrant.